Effect of Green HRM Practices, Employee Training on Efficiency Mediated by Employee Motivation at PT Pegadaian - Syifa Nur Jannah; Jati Waskito (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Environmental challenges and climate change remain pressing global concerns, pushing organizations to adopt sustainable practices, including Green Human Resource Management (Green HRM). This study explores the impact of Green HRM practices and employee training on employee efficiency, with employee motivation serving as a mediating variable. The research was conducted at PT Pegadaian Area Semarang, involving 120 respondents. The central question addressed in this study is whether Green HRM and employee training can enhance employee efficiency directly and through the mediating role of employee motivation. The research objectives are to analyze the direct impact of Green HRM and training on efficiency and examine the role of motivation as a mediator. The research utilizes the Structural Equation Modeling (SEM) technique with a Partial Least Square (PLS) approach to analyze the data. The findings reveal that Green HRM and employee training do not directly affect employee efficiency. However, both significantly influence employee motivation, which, in turn, boosts employee efficiency. These results emphasize the critical role of motivation in mediating and driving efficiency improvements through Green HRM and training initiatives.